Expression of plzfa in embryo and adult of medaka Oryzias latipes. Issue 2 (15th June 2015) - Zhao, H. B.; Zhang, X. Y.; Feng, G. Q.; Guo, M. M.; Chang, P.; Qi, C.; Zhong, X. P.; Zhou, Q. C.; Wang, J. L.
<x xml:space="preserve">Abstract</x> In this study, a homologous gene named plzfa was identified and characterized in medaka Oryzias latipes. Oryzias latipes plzfa was detected in all the tissues including brain, gill, muscle, liver, intestine, kidney, spleen, testis and ovary using reverse transcriptase (RT)‐PCR. plzfa was detected in the oocytes of the ovary and in the spermatogonia and somitic cells of the testis by in situ hybridization. plzfa had a maternal origin with continuous and dynamic expression during embryonic development. plzfa was observed in the brain, neural rod and sensor organs including the eyes, ears and nose during embryogenesis. plzfa was also detected in the neural crest, somite, pectoral fin, intestine and skin. These results indicate that plzfa is a pleiotropic gene that may play major roles in various tissues.